(untitled) (Research, Society and Development, 2019)
The preservation of the environment is one of the most relevant issues today. In view of new concerns and positive perspectives regarding the adoption of sustainable development policies, it is necessary that environmental education be treated in the daily life of individuals from a young age, thus contributing to the construction of habits and attitudes of preservation of quality of the environment to which they are inserted. This article aims to highlight how the environmental education implanted in the Crê-Ser Foundation in João Monlevade-MG, contributed to raising awareness and awareness among students. For the development of the research, we used data obtained through bibliographical research and methodologically planned meetings at the foundation, where we sought to transmit information in a playful way, from the wheels of conversations and interactive activities. With the data obtained in the foundation it was possible to perceive a cleaner and more organized environment, besides changes of behavior, that contribute to a better quality of life. Environmental Education is effective in training individuals, making them reflect and acquire knowledge about environmental practices and ways of minimizing environmental damage.